EC-WIN! Advancing Collaborative Inquiry and Partnerships - Jacqulyn Williams (21260804) (2025)
The Education City Writing and Information Network (EC-WIN) is a formalized partnership of librarians and writing center experts from five U.S. undergraduate branch campuses, i.e., Carnegie Mellon University in Qatar, Georgetown University in Qatar, Northwestern University in Qatar, Virginia Commonwealth University in Qatar, and Weill Cornell Medicine in Qatar, along with members of Hamad Bin Khalifa University and Qatar National Library. Founded through ongoing dialogue among librarians and writing specialists, EC-WIN emerged in early 2024 as a strategic response to the evolving challenges and opportunities presented by generative AI in higher education. In a series of meetings throughout the spring and fall of 2024, members co-worked on the development of a mission and vision statement. Guided by these statements, three working groups were identified as strategic initiatives to focus the forum’s activities. They include promoting first-year student success; leveraging generative AI applications in libraries; and identifying outreach and advocacy opportunities at critical inflection points. This lightning presentation explores EC-WIN’s potential as a collaborative model for interdisciplinary knowledge exchange. We will highlight how the network’s initiatives leverage collective expertise to enhance institutional impact, particularly in advancing contemporary literacies, communication and writing skills as integral to innovative teaching, learning and research. By reflecting on our progress and identifying opportunities for future engagement, we aim to foster a broader dialogue on sustaining cross-institutional partnerships that can adapt to the evolving landscape of higher education. Other Information Presentation was given at: Libraries Thriving Together in an Open Ecosystem https://www.qnl.qa/en/libraries-lead-forum-2025 License: https://creativecommons.org/licenses/by/4.0/ Conference information: Libraries Lead Forum 2025 https://www.qnl.qa/en/libraries-lead-forum-2025/agenda